2013
DOI: 10.4236/ijmpcero.2013.24018
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric Study of Coplanar and Non-Coplanar Intensity-Modulated Radiation Therapy Planning for Esophageal Carcinoma

Abstract: Purpose: To compare the dosimetric impact of coplanar intensity modulated radiation therapy (IMRT) and non-coplanar IMRT for the esophageal carcinoma. Methods: There are forty-five esophageal carcinoma patients, fifteen of whom were cervical and upper thoracic (Group 1) and thirty were middle and lower thoracic (Group 2). Gross tumor volume (GTV), clinical target volume (CTV), and organs at risk (OAR) were contoured by the chief physician in the CMS-XiO treatment planning system. For each patient, one coplanar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
(20 reference statements)
1
0
0
Order By: Relevance
“…To date, this is the first study that attempted to evaluate the dosimetric superiority of ncVMAT plans in patients with long, tube-like esophageal targets for a large group of patients (n=20). In a similar study, Li et al [16] OARs such as the lungs, heart, and spinal cord, as shown in this study. We found that the maximum doses to both the spinal cord and heart were dramatically reduced in the ncVMAT plans.…”
Section: Discussionsupporting
confidence: 83%
“…To date, this is the first study that attempted to evaluate the dosimetric superiority of ncVMAT plans in patients with long, tube-like esophageal targets for a large group of patients (n=20). In a similar study, Li et al [16] OARs such as the lungs, heart, and spinal cord, as shown in this study. We found that the maximum doses to both the spinal cord and heart were dramatically reduced in the ncVMAT plans.…”
Section: Discussionsupporting
confidence: 83%